2022
DOI: 10.3390/nu14193936
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Dutch Women Have Inadequate Iodine Status and Selenium Intake

Abstract: Iodine and selenium are essential for thyroid hormone synthesis. Iodine and selenium interact. Pregnancy increases the maternal iodine requirement. We previously reported inadequate iodine status in pregnant Dutch women. Since little is known about their selenium intake, we investigated the iodine status and selenium intake in relation to iodine and selenium supplement use during pregnancy. Iodine status was established in 201 apparently healthy pregnant women as 24 h iodine excretion (24H-UIE; sufficient if m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Dineva et al reported a median urinary iodine to creatinine ratio of 210 µg/g [26], which is above the cut-off value of 150 µg/L for insufficiency. Mayunga et al reported, however, a median ratio of 141 µg/g, where 58% of the women had insufficient iodine concentrations [99]. A total of 40% of the women used iodine-containing supplements, of which 29% used a dose of 75 µg per day and 17% a dose of 150 µg per day [99].…”
Section: Vitamin C Iron and Magnesiummentioning
confidence: 99%
“…Dineva et al reported a median urinary iodine to creatinine ratio of 210 µg/g [26], which is above the cut-off value of 150 µg/L for insufficiency. Mayunga et al reported, however, a median ratio of 141 µg/g, where 58% of the women had insufficient iodine concentrations [99]. A total of 40% of the women used iodine-containing supplements, of which 29% used a dose of 75 µg per day and 17% a dose of 150 µg per day [99].…”
Section: Vitamin C Iron and Magnesiummentioning
confidence: 99%
“…At present many pregnant Dutch women have low iodine status [ 150 ]. They also have poor selenium status and 61% are both iodine and selenium deficient [ 151 ]. Currently 88% of the global population uses iodized salt, and the number of countries with according to the World Health Organization (WHO) adequate iodine intake has nearly doubled from 67 in 2003 to 118 in 2020.…”
Section: Considerations Pertaining To Iodine and Selenium Dietary Ref...mentioning
confidence: 99%
“…And Mayunga K.C. et al reported inadequate iodine levels in pregnant Dutch women [32]. Because as there is no enough information about their selenium intake, we examined iodine status and selenium intake in relation to iodine and selenium supplementation during pregnancy.…”
Section: Introductionmentioning
confidence: 98%